2014
DOI: 10.1097/ccm.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

A Multibiomarker-Based Outcome Risk Stratification Model for Adult Septic Shock*

Abstract: Objectives Clinical trials in septic shock continue to fail due, in part, to inequitable and sometimes unknown distribution of baseline mortality risk between study arms. Investigators advocate that interventional trials in septic shock require effective outcome risk stratification. We derived and tested a multibiomarker-based approach to estimate mortality risk in adults with septic shock. Design Previous genome-wide expression studies identified 12 plasma proteins as candidates for biomarker-based risk str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 30 publications
0
89
0
Order By: Relevance
“…Along these lines, we analyzed our data on cytokine secretion, using a nonparametric hypothesis testing, followed by another different approach named classification and regression tree learning algorithm. This is a data mining methodology, used in various scientific disciplines, including, lately, in the biological and medical fields (Richette et al 2014;Wong et al 2014). By applying this nonconventional statistical strategy, we could find in our data information of interest, which had not been evidenced by the conventional approach used earlier [1].…”
Section: Introductionmentioning
confidence: 72%
“…Along these lines, we analyzed our data on cytokine secretion, using a nonparametric hypothesis testing, followed by another different approach named classification and regression tree learning algorithm. This is a data mining methodology, used in various scientific disciplines, including, lately, in the biological and medical fields (Richette et al 2014;Wong et al 2014). By applying this nonconventional statistical strategy, we could find in our data information of interest, which had not been evidenced by the conventional approach used earlier [1].…”
Section: Introductionmentioning
confidence: 72%
“…Subjects were selected from the Molecular Epidemiology of Severe Sepsis in the ICU cohort study at the University of Pennsylvania (21,22) Figures 1B and 1C). Strikingly, RBC-treated ECs also displayed marked plasma membrane loss and nuclear swelling.…”
Section: Detection Of Rip3 In Human Subjectsmentioning
confidence: 99%
“…6,7 Lactate was recently included in a multibiomarker-based outcome risk model for patients with septic shock. 8 Although hyperlactatemia has been widely recognized as a marker of tissue hypoxia/hypoperfusion, the source, biochemistry, and metabolic functions of lactate remain unclear. Recently, it was clearly suggested that hyperlactatemia could result not only from tissue hypoxia or anaerobic glycolysis but also from increased or accelerated aerobic glycolysis during the stress response.…”
mentioning
confidence: 99%